2001
DOI: 10.1128/jb.183.6.1909-1920.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the pmsCEAB Gene Cluster Involved in Biosynthesis of Salicylic Acid and the Siderophore Pseudomonine in the Biocontrol Strain Pseudomonas fluorescens WCS374

Abstract: Mutants of Pseudomonas fluorescens WCS374 defective in biosynthesis of the fluorescent siderophore pseudobactin still display siderophore activity, indicating the production of a second siderophore. A recombinant cosmid clone (pMB374-07) of a WCS374 gene library harboring loci necessary for the biosynthesis of salicylic acid (SA) and this second siderophore pseudomonine was isolated. The salicylate biosynthesis region of WCS374 was localized in a 5-kb EcoRI fragment of pMB374-07. The SA and pseudomonine biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 63 publications
2
138
0
Order By: Relevance
“…Duplicated genes indicated by light colors were detected by using a constraint of 35% identity over more than 80% of the length of the protein. for the synthesis of a siderophore related to acinetobactin and containing a salicylamide moiety 21 ( Supplementary Fig. 5).…”
Section: Toxins Against Competitorsmentioning
confidence: 99%
“…Duplicated genes indicated by light colors were detected by using a constraint of 35% identity over more than 80% of the length of the protein. for the synthesis of a siderophore related to acinetobactin and containing a salicylamide moiety 21 ( Supplementary Fig. 5).…”
Section: Toxins Against Competitorsmentioning
confidence: 99%
“…Moreover, treatment with strain WCS374 cannot induce systemic resistance in A. thaliana, whereas the application of SA does (Van Wees et al 1997). Possibly, the iron-regulated ISR by WCS374 in radish is mediated by the SA-containing siderophore pseudomonine (Mercado-Blanco et al 2001). Pseudomonine is a nonfluorescent siderophore, produced by WCS374, that was discovered when analyzing nonfluorescent mutants of this strain (Figs.…”
Section: Role Of Salicylic Acidmentioning
confidence: 99%
“…2. Structure of pseudomonine, the nonfluorescent siderophore produced by WCS374 (Mercado-Blanco et al 2001). The molecule contains histamine, a cyclothreonine moiety in the middle, and, interestingly, a SA group.…”
Section: Role Of Population Densitiesmentioning
confidence: 99%
“…Optimal suppression of pathogens occurred at levels between 10 -9 -10 -24 M. The critical level of iron at which a siderophoreproducing strain of P. putida suppressed the growth of a fungal pathogen, Fusarium oxysporium, was found to be < 10 -16 M (Neilands and Nakamura, 1991). Since the synthesis of each siderophore generally requires the activity of several gene products (Mercado-Blanco et al, 2001), it is difficult to genetically engineer bacteria to produce modified siderophores. Complementation studies of siderophore-deficient mutants of P. fluorescens M114 indicated that at least five separate genetic loci are needed to encode the enzymes involved in the synthesis of the siderophore pseudobactin M114 (O"Sullivan et al, 1990).…”
Section: Plant Growth Promoting Rhizobacteriamentioning
confidence: 99%